Implementasi Metode Famibisyauqin Dalam Proses Menghafalkan Al-Qur'an Di Pondok Pesantren El-Bayan Majenang Cilacap - Fitriatus Syaringah; Robingun Suyud El Syam; Nasokah Nasokah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The Qur'an is kalamulloh which is used as a guide to human life both physically and mentally. Allah SWT always makes it easy for his servants who want to be serious about studying the Koran, including memorizing it. However, in practice, a memorizer of the Qur'an is obliged to maintain his memorization, understand what he learns, and is responsible for implementing it in his daily life. Therefore, a method is needed in the process of memorizing the Al-Qur'an and its maintenance. This thesis aims to find out how the famibisyauqin method is implemented in the process of memorizing the Al-Qur'an at the El-bayan Majenang Cilacap Islamic Boarding School, and also aims to find out the supporting and inhibiting factors in implementing the famibisyauqin method. This research method is to use a descriptive qualitative approach. The data sources were taken through subjects, Ustadz/ustadzah and hufadz students. Data collection techniques used were observation, interviews and documentation. Data is analyzed by reducing relevant data, explaining the data and drawing conclusions. From the research results it can be concluded that: 1) The implementation of the famibisyauqin method in the process of memorizing the al-Qur’an at the El-Bayan Islamic Boarding School is carried out classically and individually. Classical learning is applied when memorization is given to the ustadz/ustadzah, while individual learning is the muroja'ah activity of memorizing the reading of the Al-Qur'an within seven days which is carried out by each student. 2) the famibisyauqin method applied at the El-Bayan Islamic Boarding School is an effort to improve the quality of students' memorization and train students to maintain the continuity of the Al-Qur'an as a sense of responsibility in memorizing the Al-Qur'an, the implementation of which has been targeted at every week of the system